Scoping systematic review on the extent, nature and quality of evidence underlying ophthalmic and paraophthalmic education. Issue 1 (19th December 2016) - Williams, Michael; Boohan, Mairead; Thurston, Allen
Abstract : Background: Effective education of relevant professionals underpins provision of quality eye healthcare. Objectives: This scoping systematic review had 2 aims: first to investigate the extent and nature of scholarly output published on ophthalmic and paraophthalmic education, and second to focus on the quality of reporting of randomised controlled trials (RCTs) identified. Study selection: A search strategy was created and applied to PubMed. Any scholarly publications on any aspect of education of those involved in the care of patients with visual problems as the main theme or context was selected. Predefined data were extracted. Findings: Of 255 studies included, the most common type of scholarly publications were descriptions of an educational innovation, opinion pieces and descriptive studies. RCTs made up 5.5% of the sample. Most of the 14 RCTs failed to report most of the items recommended in the CONSORT guidelines. Conclusions: This review highlights the need for investigators, ethical committees and journals to insist on a better quality of RCT conduct than is presently apparent, but also that clinicians should not be blind to the strengths of non-RCT-based studies in the field of education.